Regional processes in Hungary - From PHARE to Smart specialisation - Viktória Józsa (DETUROPE)
Europeanisation and regionalization, European convergence versus local divergence are important and timely questions as regards the future of EU cohesion policy, that originally aimed to reduce economic, social and territorial inequalities. Recently, it does not solely support regional development and stimulate modernization processes, but also aims to advance competitiveness, job creation, innovation, and sustainable growth and development (Europe 2020 strategy), especially at the sub-national level. The comparison of regional processes, institutional systems, experience and the originating potential future scenarios of transition economies are interesting but yet under-examined fields of study. Is there a specific way (trajectory) of regionalization in transition economies, or practices vary from country to country? Do EU level policy changes affect national and sub-national level institutions and processes and if yes, for what extent? PHARE programmes were introduced in the early 1990s, short after the change of regime, and following the EU accession, Structural Funds have become the main public financial instruments in these countries, accompanied with a massive foreign direct investment flow. The subsequent EU programming periods and the connected terminology have been predominantly shaping regional policy in these countries; Operational Programmes, Action Plans, Logical Framework Approach, Project fiches, Regional Innovation Strategies, Local Action Groups, Competitiveness Poles, Clustering, Smart Specialisation, Re-industrialisation are only a few keywords that describe this era. The objective of this study is to present a qualitative framework to the evaluation of the period from 1990 to 2015 in Hungary, as a case study of the transition economies, with the identification of the most important milestones and tendencies of regionalization. The relevance of the research is supported by the recent elimination of the NUTS II (regional) level institutional system in the country, and the relocation of ESIF management to the NUTS III (county) level. This process poses the question if Hungary is a trendsetter in Central and Eastern Europe with this practice, or a unique case. The contribution to the state-of-the-art is a qualitative, thorough presentation of the processes, focusing on the administrative and institutional aspects that can on one hand provide a better understanding and secondly, can form an inspiring basis and qualitative methodology for further research on past and future territorial processes and the future of Cohesion policy in the CEE region.